Design and Construction of an AC Automatic Light Sensitive Switch System to Control Bulbs Inside Buildings - F.E., Aboche; B.N., Ndom; A., Achimugu; S., Saleh; J.J., John; A.A., Kozah (Darul Yasin Al Sys, 2026)
Electrical energy wastage remains a persistent challenge in modern buildings, particularly where lighting systems rely on manual switching that requires continuous human intervention and often results in bulbs being left on during the daytime or unavailable when needed at night. This study aimed to design and construct a prototype automatic light-sensitive switch system for controlling alternating-current lighting points in buildings such as lecture halls, classrooms, and offices in order to reduce unnecessary electricity consumption. The system was developed using a Light Dependent Resistor (LDR) as a photosensor and a relay-based switching mechanism to detect changes in environmental brightness and darkness and automatically switch bulbs on at sunset and off at sunrise. The methodological process was carried out in sequential stages comprising software simulation, component assembly and testing on a breadboard, soldering, final testing, and packaging of the prototype. The findings indicate that the developed system can automatically respond to ambient light conditions and control lighting operation without manual intervention. The prototype is projected to reduce building electricity costs by approximately 50% compared with a manual switching system, while also improving bulb lifespan and operational efficiency. The study concludes that an automatic light-sensitive switching system offers a practical and efficient solution for minimizing electrical energy wastage in residential and institutional settings. Its contribution lies in providing a simple, low-cost, and functional prototype that supports energy conservation and more efficient lighting management in buildings.